Inhibition of SARS-CoV-2 3CL Mpro by Natural and Synthetic Inhibitors: Potential Implication for Vaccine Production Against COVID-19 - Ullah, Anwar; Ullah, Kifayat (Frontiers in Molecular Biosciences, 2021)
COVID-19 has created a pandemic situation all over the world. It has spread in nearly every continent. Researchers all over the world are trying to produce an effective vaccine against this virus, however; no specific treatment for COVID-19 has been discovered -so far. The current work describes the inhibition study of the SARS-CoV-2 main proteinase or 3CL Mpro by natural and synthetic inhibitors, which include 2S albumin and flocculating protein from Moringa oleifera (M. oleifera) and Suramin. Molecular Docking study was carried out using the programs like AutoDock 4.0, HADDOCK2.4, patchdock, pardock, and firedock. The global binding energy of Suramin, 2S albumin, and flocculating proteins were −41.96, −9.12, and −14.78 kJ/mol, respectively. The docking analysis indicates that all three inhibitors bind at the junction of domains II and III. The catalytic function of 3CL Mpro is dependent on its dimeric form, and the flexibility of domain III is considered important for this dimerization. Our study showed that all three inhibitors reduce this flexibility and restrict their motion. The decrease in flexibility of domain III was further confirmed by analysis coming from Molecular dynamic simulation. The analysis results indicate that the temperature B-factor of the enzyme decreases tremendously when the inhibitors bind to it. This study will further explore the possibility of producing an effective treatment against COVID-19.